Housework, wages, and the division of housework time for employed spouses - Hersch, Joni; Stratton, Leslie S. (American Economic Review, 1994)
While the popular press may have declared housework passe with the advent of the two-income household (see Housework is Obsolescent by Barbara Ehrenreich [1993] for one such example), the facts indicate that housework continues to consume a substantial amount of time, particularly for women. While estimates vary widely depending on the sample examined and the methods used to generate the information, representative values of housework time range around 6-14 hours per week for men and 20-30 hours for women. Since wages are likely to be influenced both directly and indirectly by the time and effort devoted to other activities, and since gender differences in household responsibilities are significant and often assumed to be a driving force behind gender earnings differentials, decisions regarding the overall amount of time spent on housework and the division of that time within the household are important ones. The goal of this paper is to shed some light on these allocation decisions. We begin by discussing the various methods by which time and effort spent on housework may affect wages and summarize the available empirical evidence. Overall, the empirical evidence indicates that time spent on housework has a negative effect on wages, an effect which is most pronounced for women. We next examine the amount of time spent on housework and the division of that time between working spouses. To do so, we draw upon the human-capital literature and the bargaining literature to construct simple regression equations for time spent on housework by each spouse as well as the share of housework time contributed by the husband. The results indicate that husbands do less housework than their wives as their relative earnings and hours spent in the labor market increase.